Idiopathic inflammatory myopathy: From muscle biopsy to serology - Ritu Verma; Vimal Kumar Paliwal (Indian Journal of Rheumatology)
Idiopathic inflammatory myopathies (IIMs) are heterogeneous group of muscle disorders characterized by variable degree of muscle weakness and muscle inflammation. Various classification systems have been proposed for myositis. However, there remains a diagnostic uncertainty due to the presence of overlapping clinical and pathological features. Similar treatment outcomes to immunosuppressant drugs further add to diagnostic confusion. Introduction of myositis-specific and myositis-associated autoantibodies has widened the disease spectrum of IIMs. Despite being very crucial for the diagnosis and classification of myositis, these autoantibodies are not always present. Therefore, histopathological features and immunohistochemical markers are considered gold standard for the diagnosis of myositis. A correct diagnosis has important clinical and therapeutic implications. In this review, we have focused on salient clinicopathological features and newly developed serological markers in major subtypes of IIMs.